Hantavirus infection: an emerging infectious disease causing acute renal failure - Krautkrämer, Ellen; Zeier, Martin; Pljusnin, Alexander (Kidney international, 2013)
The function of the kidney with its highly differentiated and specialized cell types is affected by infection with several viruses. Viral infections of the kidney have a negative impact not only on patients undergoing renal transplantation and immunosuppression. Besides the increasing number of patients suffering from HIV-associated nephropathy, another group of viruses infects immunocompetent patients and induces renal failure. Hantaviruses belong nowadays to the emerging zoonoses that increase in number and geographic distribution. The viruses are distributed worldwide in endemic areas and distribution seems to expand. Together with the increase in the number of cases in the last few years, the understanding of epidemiology and pathology has deepened and some concepts had to be changed. Symptoms and mortality vary between species. The classification refers to geographical distribution: New World hantaviruses causing hantavirus cardiopulmonary syndrome (HCPS) and Old World hantaviruses causing hemorrhagic fever with renal syndrome (HFRS). Indeed, in most HFRS cases, the kidney is mainly affected and HCPS is characterized by cardiopulmonary involvement. But the picture of strict organ tropism is changing and reports of pulmonary findings and nonrenal manifestations in infections with Old World hantaviruses are increasing. However, the overall symptoms—vascular alterations and leakage—that are responsible for organ failure are characteristic for all diseases caused by hantaviruses.